2013
DOI: 10.1016/j.jcjd.2013.08.183
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salvia Hispanica L. Seeds on Weight Loss in Overweight and Obese Individuals with Type 2 Diabetes Mellitus

Abstract: There is growing interest in the potential role of omega-3/fibre-rich seeds in attenuating obesity and other cardiovascular disease (CVD) risk factors in individuals with type 2 diabetes mellitus (T2DM).Preliminary data suggests that consumption of white Salvia hispanica L. (Salba ® ) seeds prolongs satiety and may aid weight loss. This randomized, double-blind, parallel study assessed the efficacy and safety of Salvia hispanica in overweight/obese individuals with T2DM on weight, body composition, glycemic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 326 publications
(218 reference statements)
1
6
0
2
Order By: Relevance
“…The applicants provided eight articles on human studies (Nieman et al, 2009Vuksan et al, 2010Vuksan et al, , 2017aIllian et al, 2011;Guevara-Cruz et al, 2012;Jin et al, 2012;Ho et al, 2013) and three reviews (Ulbricht et al, 2009;Ali et al, 2012;Teoh et al, 2018). EFSA retrieved six additional human studies in literature search (Brissette et al, 2013;Toscano et al, 2014Toscano et al, , 2015Nieman et al, 2015;Ayaz et al, 2017;Vuksan et al, 2017b) and three review articles (De Souza Ferreira et al, 2015;Parker et al, 2018;Grancieri et al, 2019).…”
Section: Toxicological Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…The applicants provided eight articles on human studies (Nieman et al, 2009Vuksan et al, 2010Vuksan et al, , 2017aIllian et al, 2011;Guevara-Cruz et al, 2012;Jin et al, 2012;Ho et al, 2013) and three reviews (Ulbricht et al, 2009;Ali et al, 2012;Teoh et al, 2018). EFSA retrieved six additional human studies in literature search (Brissette et al, 2013;Toscano et al, 2014Toscano et al, , 2015Nieman et al, 2015;Ayaz et al, 2017;Vuksan et al, 2017b) and three review articles (De Souza Ferreira et al, 2015;Parker et al, 2018;Grancieri et al, 2019).…”
Section: Toxicological Informationmentioning
confidence: 99%
“…Other studies had a duration of up to half a year (Brissette et al, 2013;Vuksan et al, 2017a) with the number of participants ranging from 10 to 77 (Vuksan et al, 2017a) and average dose levels of 30 g/day. Some of these studies, although not primarily designed to assess the safety of chia seeds, reported safety-related parameters such as anthropometrics (body mass and composition), blood pressure, clinical chemistry (urea, creatinine, alanine transaminase (ALT), serum lipid profile, serum glucose and lactate, serum cortisol, inflammation markers) and haematology parameters (complete blood counts, prothrombin time).…”
Section: Toxicological Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Toscano et al (2014) had observed only a within-group change in SBP after 35 g/day chia seed testing for three months, compared to wheat bran placebo control. No between-group differences in SBP were observed when comparing the use of chia seeds to oat bran as a placebo control (Brissette et al, 2013). This is not surprising to observe no differences in the BP when chia seeds, a high-fiber test food was compared to an equal amount of fiber-containing placebo control, either wheat or oat bran.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that have combined chia seed supplementation along with a hypocaloric diet observed higher body weight reductions. For example, Brissette et al (2013) demonstrated significant weight reduction by feeding either ground or whole chia seeds in baked bread along with a daily reduction of 500 Kcal from the usual diet. Vuksan et al (2017b) reported a significant percent loss of body weight in participants consuming a hypocaloric diet of 25% Kcal reduction from the daily energy requirement.…”
Section: Discussionmentioning
confidence: 99%